The effect of informational technology towards the declined of moral values among teenagers the solution according to Siyasah Syariyyah - Husni, Ahmad Muhammad (Zes Rokman Resources (2131022-P), 2021)
The rapid development of information technology (ICT) has had a profound impact on community especially for Muslim teenagers. The quick growth of informational technology makes the world today seems to be smaller. This matter hence brings negative implication towards the teenage morality. The purpose of this study is to investigate how far the advancement of information technology has a negative impact on the teenagers’ behavior and to identify the level of restriction imposed by various parties in fighting the moral decline that results from the spreading of uncontrolled information. This study uses library study method and sources from internet, statistic material from library, act and reports on this issue were analyzed to gain a better understanding of the implications of the speedy growth of information technology in the country and its impact on teenagers. This study found that the open minded and unlimited acceptance of information technology has contributed to the problem of moral decline, especially among the youth. Furthermore, this study proposes several appropriate policies based on siyāsah syar’iyyah so that information technology management can be done in the right way.